Population Growth and GDP Growth in Pakistan: Three Models (The Pakistan Development Review, 2022)
Three dynamic population—GDP growth models, are developed, each based on a CobbDouglas production function. The first model simulates the effects of average wealth on population and GDP growth, whereas the second model simulates the effects of wealth inequality. The third model simulates the effects of a demographic dividend. The models successfully simulate the observed historical and projected future population and GDP of Pakistan. Scenario simulations with the first model with higher and lower population growth rates result in larger or smaller GDP, respectively, but smaller or larger GDP per capita at 2100. The inequality model simulations with reducing or increasing inequality result in a smaller or larger population, respectively, and smaller or larger GDP, but higher or lower GDP per capita at 2100. The demographic dividend model simulations result in larger GDP and higher GDP per capita than the other models.